Fewer protective cytotoxic T-cell epitopes than T-helper-cell epitopes on vesicular stomatitis virus. - Kündig, T; Castelmur, I; Bachmann, M; Abraham, D; Binder, D; Hengartner, H; Zinkernagel, R (1993)
Cytotoxic T-lymphocyte (CTL) and T-helper-cell responses in various mouse strains were monitored. Protective CTL responsiveness against three proteins of vesicular stomatitis virus was H-2 linked and inducible only in half of the 15 combinations tested (each of five H-2 haplotypes combined with each of three viral proteins), whereas biologically relevant T-helper-cell responses were inducible in all. This suggests that vesicular stomatitis virus exhibits more T-helper-cell than CTL epitopes.